Growth and Yield Performance of Shingi, Heteropneustes fossilis and Koi, Anabas testudineus in Bangladesh under Semi-Intensive Culture Systems (International Journal of Agricultural Research, Innovation and Technology, 2013)
Production potential of shingi, Heteropneustes fossilis and koi, Anabas testudineus in polyculture were assessed at a stocking density of 2, 47,000 and 3, 70,500 ha-1, respectively in treatment T1 and T2. Monoculture of H. fossilis and A. testudineus was designed at a stocking density of 2, 47,000 ha-1 in treatment T3 and T4, respectively. Culture period of shingi was 120 days and koi was 100 days in all treatments. All fingerlings were of the same age at stocking, with a mean weight of 2.54±0.08 g for shingi and 0.50±0.01 g for koi, respectively. Commercial fish feeds (30.0% crude protein) supplied at the rate of 100 to 5% of total biomass twice daily. Fish production in treatment T1, T2, T3 and T4 were 18,803±111, 12,388±115, 10,042±5 kg ha-1 day-120 and 22,176±7 kg ha-1 day-100, respectively. The feed conversion ratio (FCR) was significantly (P